Implementation of Indonesian Defense Diplomacy in the South Pacific Region - Mahroza, Jonni; Widjayanto, Joni; Yulivan, Ivan; Prakoso, Lukman Yudo; Setiadi, Muhammad Ikmal (PT FORMOSA CENDEKIA GLOBAL, 2023)
Domestically, Indonesia is also facing the dynamics of separatist movements and responding to cases of human rights violations in Papua, threats coming from support from Pacific countries for Papuan independence which then led Indonesia to create a